Realidade virtual na reabilitação de pacientes com quadro doloroso do complexo do ombro: avaliação da dor e adm - Brepohl, Polyana Cristina Alves (2023)
The shoulder joint is one of the most complex joints in the human body. Due to its complexity, the treatment for shoulder complex tendinopathies can become extensive and monotonous for the patient. The search for ways to increase patient adherence to treatment is a challenge for physical therapists. The use of Virtual Reality has been increasingly studied in different fields of treatment, especially in physiotherapy. Although VR is a well-known technological resource, it is necessary to better understand its applications in rehabilitation. The objective of our study was to evaluate the effectiveness of the use of VR in a patient with painful shoulder discomfort, through the measurement of ROM improvement, utilizing joint goniometry, as well as to evaluate pain reduction, using visual analog pain scale (VAS). Our work consists of a randomized controlled clinical study, with a total of 50 participants divided into two independent groups: one using conservative treatment (26 participants), and the other using VR as treatment (24 participants). After a total period of 18 treatment sessions, the results obtained from our study do not show a significant difference in ROM gain between treatment groups. Regarding pain control, the VR group had a better response in reducing pain, however, this cannot be considered as a significant difference between groups. Furthermore, when measuring treatment adherence, the VR group had a lower rate of participant dropout (6,35%), compared to the conventional treatment (14,29%). These results confirm that the use of VR in shoulder rehabilitation can increase patient adherence to the treatment while allowing the possibility of recovery for the patient, providing motivation to the patient during the treatment period.